Enantiomeric Recognition of α-Aminoacids by a Uranyl Salen-Bis-Porphyrin Complex - Gangemi, Chiara M. A.; Rimkaite, Ugne; Cipria, Federica; Trusso Sfrazzetto, Giuseppe; Pappalardo, Andrea (Frontiers in Chemistry, 2019)
A novel uranyl salen-bis-porphyrin complex, in which two porphyrin subunits and salen moiety were directly linked, was synthesized for the recognition of tetrabutylammonium (TBA) amino acids. This uranyl salen complex, due to the presence of porphyrins with their fluorescence properties, represents the first example of a luminescence of uranyl salen complexes. UV/Vis measurements indicate the formation of 1:1 host–guest complexes, whereas UV-vis and fluorescence studies revealed that this complex acts as a receptor for the enantiomeric recognition of α-aminoacids derivatives, with high association constants and an excellent enantiomeric discrimination between the two enantiomers of phenylalanine–TBA.